MANAJEMEN PESANTREN DALAM PERSIAPAN PEMBELAJARAN 5.0 - Dea Ariani; Syahrani Syahrani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Management is basically a process carried out by a person in managing activities carried out by individuals or groups. The focus of this study is to find out how the Rasyidiyah Khalidiyah Islamic boarding school in dealing with learning in the 5.0 era of society and what needs to be prepared in the face of 5.0 learning preparation and the results show that Islamic boarding schools in facing the 5.0 era indirectly require every institution education to improve itself, especially in the field of education quality management. This is based on the results that have been researched which lead to several conclusions, namely the need for quality education must be balanced with the demands of the 5.0 era, and Islamic boarding schools are able to present the best curriculum for the development of education in the current 5.0 era, as well as increasing quality human resources in the current era of 5.0. Islamic boarding schools prove that these educational institutions are able to compete in the 5.0 era with other educational institutions.